Ethno-demographic development of Northern Kazakhstan from 1999 to 2022: history, issues and prospects - Ilyassova, G.S.; Sadykov, T.S.; Zherebtsov, I.L. ("Акад. Е.А. Бөкетов ат. Қарағанды ун-ті" КЕАҚ баспасы, 2023)
The article analyzes the ethno-demographic development of Northern Kazakhstan on the basis of statistical data from the Bureau of National Statistics of the Agency for Strategic Planning and Reforms of the Republic of Kazakhstan. The purpose of the article is based on the analysis of historical factors affecting the ethnographical development of Northern Kazakhstan, to study new processes and trends taking place in the field of ethno-demographic processes on the territory of Northern Kazakhstan in 1999-2022. The article examines in detail the population structure of Northern Kazakhstan according to the 1989, 1999 and 2021 censuses. The authors come to the conclusion that at the present stage, the Kazakh ethnic group has managed to regain its lost positions to some extent by increasing its number and specific weight in Northern Kazakhstan and one of the main directions for improving the demographic development of the northern regions is the implementation and improvement of resettlement programs from the southern regions to the northern ones.
1999-2022 жж. Солтүстік Қазақстанның этнодемографиялық дамуы: тарихы, мәселелері және болашағы
Этнодемографическое развитие Северного Казахстана в 1999–2022 годы: история, проблемы и перспективы
Keywords: Northern Kazakhstan; demography; ethno-demography; population; ethnos; population dynamics; population census